A simple strategy to tune the lateral response of unbonded Fiber Reinforced Elastomeric Isolators (FREIs). (1st November 2020) - Tran, Chris; Calabrese, Andrea; Vassiliou, Michalis F.; Galano, Simone
Highlights: Fiber Reinforced Elastomeric Isolators with horizontal holes are numerically studied. The aim is to make them suitable for isolating low cost buildings. The holes decrease the initial stiffness of the bearings. Under large deformations, the holes close and the standard FREIs instability disappears. More research is needed to study different hole configurations. Abstract: The study of Fiber Reinforced Elastomeric Isolators (FREIs) has gained momentum over the last decade for their potential to be adopted directly under the foundation of masonry buildings with no need for costly rigid diaphragms and transfer structures, which are required for the application of conventional base isolation (BI) devices. While the possibility of base isolating masonry structures with no diaphragms at the isolation level is fascinating, this requires FREIs with a tunable response in all 3 directions (i.e., devices that can be engineered to perform in a specific way in each direction of loading). It is known that unbonded FREIs exhibit softening and instability under large displacements. While softening of the bearings is beneficial because it reduces the force demand on structural elements, instability is not. This is particularly true as the unstable branch of FREIs is followed by a sharp hardening response. With the aim of contributing (i) towards the development of tunable FREIs and (ii) towards the development of FREIs with tunable hardening under large lateral deformations, this manuscript describes the findings of a wide set of Finite Element Analyses (FEAs) performed to assess the effectiveness of modifying the stiffness and the lateral response of FREIs through lateral holes. Results of the analyses show that, a simple to implement strategy can be used to tune the lateral response of FREIs to a desired hardening and lateral displacement capacity. The findings of this work constitute a step towards the development of scalable technologies for the isolation of non-engineered buildings in developing regions of the world.